Push-out tests on novel enhanced C-channels in steel-concrete-steel sandwich structures using ultra-high performance concrete. (June 2021) - Yan, Jia-Bao; Hu, Huitao; Wang, Tao
Abstract: This paper firstly developed steel-UHPC-steel sandwich structures (SUSSSs) with new enhanced C-channels (ECs). Shear behaviours of ECs embedded in ultra-high performance concrete (UHPC) were firstly investigated by a testing program with 14 specimens. The test results primarily reported the failure mode, shear strength, and shear-slip behaviours of ECs in UHPC. The ECs in UHPC exhibited a successive shear fracture of external bolts and C-channels, and a ductile shear-slip behaviour with a maximum slip capacity exceeding 6 mm. These test results also revealed the effects of length, height, and layout of the C-channel, and concrete core strength on shear behaviour of ECs. Theoretical models were also developed to describe the load-slip behaviour and predict ultimate shear resistances of novel EC connectors in UHPC. The validations against reported tests exhibited that the modified code equations greatly overestimated ultimate shear resistances of ECs, and the developed theoretical models predicted well the shear-slip behaviour and ultimate shear resistances of ECs in UHPC. The average prediction discrepancy for the developed theoretical model is only 5% with a small standard deviation of 0.06 for the 12 reported tests.